Palliative care access and use among homeless individuals: a scoping review - Ashley Rodericks-Schulwach; Ravi Gokani; Lynn Martin (BMC Palliative Care)
Abstract Background Homeless individuals experience severe health inequalities, increased rates of disease, and premature mortality. Yet the provision of palliative care for homeless individuals faces distinct challenges. The purpose of this scoping review was to understand previous research on the provision of palliative and end-of-life care for homeless populations and to clarify current knowledge about the unique needs and recommendations for care provision to this group. Methods A scoping review was conducted using PubMed, CINAHL, Embase (via Elsevier), and Web of Science databases. Peer-reviewed articles were included if they focused on palliative care in homeless populations and were published in English on or after January 1, 2010. Results Forty-five publications met the inclusion criteria. We first present the characteristics of these 45 studies, including country of origin, study design, the setting in which data were collected, sample size and characteristics, and terminology used. We then present a synthesis of study findings in three related themes: (1) the importance of the relationship between homeless individuals and healthcare staff; (2) provider-side barriers to palliative care access; and (3) the promise and perils of integrated models for palliative care provision for homeless individuals. Conclusions Homeless individuals experience unique needs and challenges when accessing palliative care. Recommendations include future research into the experience of specific sub-populations within homelessness, inter-disciplinary initiatives and models of PC provision, and specialized staff training to work with this population.